Efek Globalisasi Yang Dihadapi Masyarakat Kontemporer Terhadap Perekonomian - Khoirunisa Wahida; Hoirul Uyun; Didit Kurniawan Wintoko (Lembaga Pengembangan Kinerja Dosen, 2023)
Globalization is a process of international integration that occurs due to the exchange of worldviews, products, thoughts, and other aspects of culture. Globalization has become a significant phenomenon in contemporary society and has had a great impact on the economy. One of the main impacts of globalization on the economy of contemporary societies and the acceleration of international trade. In addition, globalization has encouraged a freer flow of investment between countries. But the effects of globalization on the economy also pose challenges that need to be addressed. Increased global competition could threaten the survival of weaker sectors of the local economy. Local companies have to compete with multinationals that have greater resources, more advanced technology, and lower production costs. This can lead to a decline in local employment and difficulty for traditional sectors to survive. In addition, the effects of globalization also create greater economic inequality. Not all segments of contemporary society can access the same opportunities and benefits from globalization. Income inequality, social inequality, and economic inequality may increase, especially between groups connected to the global economy and groups. The impact of globalization on culture has also raised concerns about the loss of local cultural identity. Amid the influence of dominant global cultures, there is a risk that local traditions, languages and values become marginalized or forgotten.